1999
DOI: 10.1097/00000374-199901000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prenatal Exposure to Alcohol on the Release of Adenocorticotropic Hormone, Corticosterone, and Proinflammatory Cytokines

Abstract: Prenatal alcohol exposure has been shown to produce hyperresponsiveness of the hypothalamic-pituitary-adrenal (HPA) axis to immune challenges. Because cytokines, which are released in response to immune challenges, are known to activate the HPA axis, this study determined whether altered release of cytokines contribute to the HPA hyperresponsiveness to immune challenges observed after prenatal alcohol exposure. Pregnant dams were exposed to alcohol vapors (6-7 hr daily) between days 7 and 18 of gestation. At p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…In studies to date, including our own, HPA hormone levels have been measured primarily at the circadian trough, and typically without regard to estrous cycle stage (Kim et al, 1999; Lee and Rivier, 1996; Weinberg, 1988; 1992a). In the present report, by factoring in stage of estrous cycle, we unmasked differences in basal CORT among prenatal groups, and found that basal CORT levels varied as a function of prenatal treatment and estrous cycle stage.…”
Section: Discussionmentioning
confidence: 99%
“…In studies to date, including our own, HPA hormone levels have been measured primarily at the circadian trough, and typically without regard to estrous cycle stage (Kim et al, 1999; Lee and Rivier, 1996; Weinberg, 1988; 1992a). In the present report, by factoring in stage of estrous cycle, we unmasked differences in basal CORT among prenatal groups, and found that basal CORT levels varied as a function of prenatal treatment and estrous cycle stage.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while HPA hyperresponsiveness is a robust phenomenon, sex differences in response are often observed depending on the nature and intensity of the stressor, time course of testing, and hormonal endpoint measured (Weinberg, 1985; Weinberg, 1992a; Weinberg, Taylor, and Gianoulakis, 1996; Weinberg et al, 2008). For example, both PAE males and females exhibit increased CORT, ACTH and/or β-EP (Weinberg, 1988; Weinberg, 1992a; Weinberg et al, 1996), as well as increased immediate early gene and CRH mRNA levels (Kim, Turnbull, Lee, and Rivier, 1999; Lee, Imaki, Vale, and Rivier, 1990; Lee, Schmidt, Tilders, and Rivier, 2000; Gabriel, Glavas, Ellis, and Weinberg 2005), in response to stressors such as repeated restraint, footshock, and immune challenges. PAE males and females also both show deficits in habituation to repeated restraint, although patterns of response may differ for the different HPA hormones measured (Weinberg et al, 1996).…”
Section: Prenatal Alcohol Exposure and Hpa Dysregulationmentioning
confidence: 99%
“…Animal models of prenatal alcohol exposure (PAE) support and extend the clinical findings. Increased susceptibility to infections (Grossmann et al, 1993; McGill et al, 2009) and malignancies (Gottesfeld and Abel, 1991), deficits in immune organ development (Bray et al, 1993; Ewald and Frost, 1987; Ewald and Walden, 1988; Redei et al, 1989), decreased splenic lymphocyte, T lymphoblast, and B cell proliferative responses to stimulation (Gottesfeld et al, 1990; Jerrells and Weinberg, 1998; Weinberg and Jerrells, 1991; Wolcott et al, 1995), blunted LPS-induced febrile responses (Taylor et al, 1999), dampened cytokine responses to immune challenge (Chiappelli et al, 1997; Kim et al, 1999; Lee and Rivier, 1993), and a more severe and prolonged course of inflammation in an adjuvant-induced arthritis model (Zhang et al, 2012) have been reported in models of in utero alcohol exposure [reviewed in Bodnar and Weinberg 2013].…”
Section: Introductionmentioning
confidence: 99%